2019
DOI: 10.1002/ldr.3380
|View full text |Cite
|
Sign up to set email alerts
|

Drivers of soil carbon stabilization in oil palm plantations

Abstract: Increasing soil organic carbon (SOC) in agroecosystems is necessary to mitigate climate change and soil degradation. Management practices designed to reach this goal call for a deeper understanding of the processes and drivers of soil carbon input stabilization. We identified main drivers of SOC stabilization in oil palm plantations using the well‐defined spatial patterns of nutrients and litter application resulting from the usual management scheme. The stabilization of oil palm‐derived SOC (OP‐SOC) was quant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 45 publications
(63 reference statements)
4
21
0
Order By: Relevance
“…Our study also revealed that SOC stability at the surface gradually decreased as the recovery years increased. In general, SOC stability is susceptible to vegetation coverage, litter, root exudates, fine root, and soil environmental conditions (Fontaine et al, 2007;Johanna et al, 2019). During the early restoration stages, vegetation composition and diversity were comparatively simple, the community structure was unstable, and soil organic matter input from , 2013).…”
Section: Effect Of Recovery Years On Carbon Sequestration and Soc mentioning
confidence: 99%
See 1 more Smart Citation
“…Our study also revealed that SOC stability at the surface gradually decreased as the recovery years increased. In general, SOC stability is susceptible to vegetation coverage, litter, root exudates, fine root, and soil environmental conditions (Fontaine et al, 2007;Johanna et al, 2019). During the early restoration stages, vegetation composition and diversity were comparatively simple, the community structure was unstable, and soil organic matter input from , 2013).…”
Section: Effect Of Recovery Years On Carbon Sequestration and Soc mentioning
confidence: 99%
“…This may lead to poor permeability and weak sunlight, which are not conducive to the growth and reproduction of soil aerobic microorganisms. In addition, according to Johanna et al (2019), SOC stabilization was mainly driven by carbon inputs from fine roots. It is possible that the HR has a large quantity fine roots which may promote the decomposition and transformation of SOC.…”
Section: Effect Of Soil Depths and Restoration Types On Carbon Sequmentioning
confidence: 99%
“…These are typically pruned manually twice a year and green fronds may also be pruned during harvesting to access fruit bunches (Corley and Tinker, 2015). These are stacked in piles or rows, therefore significant aboveground C inputs occur only within the vicinity of these frond piles in mature plantations (Ruegg et al, 2019). Leguminous cover crops may also be planted in in young plantations to stabilize soils and improve fertility (Luke et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the higher degradability of GM and Str, the stoichiometry of the input may be responsible for the very low C retention of these two amendments (Table 1). Soil amendments with high C-to-nutrient ratios are expected to reduce the microbial C use efficiency and to promote nutrient mining in SOM [61][62][63]. The stronger increase in phosphatase and chitinase activities compared to glucosidase activities in GM and Str suggests a lack of nutrient availability for microbial communities [64].…”
Section: Discussionmentioning
confidence: 99%